John Hays Hammond papers - Hammond, John Hays, 1888-1965.
Correspondence, notebooks, technical papers, legal briefs, chronologies, printed matter, sketches, annotated photographs, and other papers relating to Hammond's scientific career and inventions. Subjects include Hammond's basic experiments in radio control, frequency modulation, intermediate frequency, triode electron tube, and the Elmer Ambrose Sperry dispute on inertial guidance patents. Correspondents include Ernst Fredrik Werner Alexanderson, Alexander Graham Bell, Lee De Forest, Irving Langmuir, and Nikola Tesla.
Inventor and scientist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Alexanderson, Ernst Fredrik Werner, -- 1878-1975 -- Correspondence; Bell, Alexander Graham, -- 1847-1922 -- Correspondence; De Forest, Lee, -- 1873-1961 -- Correspondence; Langmuir, Irving, -- 1881-1957 -- Correspondence; Sperry, Elmer Ambrose, -- 1860-1930.; Tesla, Nikola, -- 1856-1943 -- Correspondence; Electron tubes; Inertial navigation systems -- Patents; Radio -- Research; Radio frequency modulation; Inventors; Scientists